PERAN PEMBELAJARAN IPS DALAM MENCEGAH KEKERASAN SEKSUAL DI SMP NEGERI 5 SEMARANG - Nuraini, Siti; Carolina Sasea, Sanita (Penerbit Lafadz Jaya, 2025)
This study aims to analyze the role of social studies learning in preventing sexual violence and the role of social studies teachers in improving students' understanding of sexual violence prevention at SMP Negeri 5 Semarang. The background of this study is based on the high number of cases of sexual violence in educational environments, especially among adolescents or junior high school students. The approach used in this study is descriptive qualitative with data collection techniques namely through observation, interviews, and documentation. The results of the study indicate that social studies learning has strategic potential in improving students' understanding of sexual violence prevention, especially through social interaction material that discusses social contact, communication, and boundaries in interactions. Social studies teachers play an important role in integrating social studies material with sexual violence prevention material to ensure its relevance. The integration of the material includes the creation of RPM (in-depth learning plan) modules, material preparation, creation of learning media, and implementation of learning in the classroom. The results of sexual violence prevention education show that students who initially did not understand sexual violence, now understand sexual violence and its prevention.